Prevalence and Psychosocial Correlates of After-School Activities among Chinese Adolescents in Hong Kong - Ma, Cecilia M. S.; Shek, Daniel Tan Lei (Frontiers in Public Health, 2014)
Using a cross-sectional design, this study a) explores the prevalence of after-school activities among Chinese early adolescents and b) assesses the relationships between participation in after-school activities, personal well-being and family functioning. A total of 3,328 Grade 7 students (mean age = 12.59 years, SD = 0.74) completed a self-administered questionnaire. Results showed that the majority of adolescents returned home under adult supervision. Further analyses showed the associations between after-school activities, positive youth development qualities, academic and school competence, family functioning and risky behavior. Implications regarding efforts aimed at designing high quality and structured after-school youth programs are discussed.